Automatic Control and Computer Sciences - Greitans, Modris; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
Automatic Control and Computer Sciences is devoted to: Control methods, modeling and identification of technological processes in the field of industry and artifical intellect in control systems. Network information technologies, information security, statistical methods of data processing, distributed artificial intelligence, complex systems modeling. Signal and image digitization and methods of their analysis, signal processing in technology, medicine, geophysics, and astrophysics, image recognition.
Keywords: Microprogramming; Control Structures and Microprogramming